Pemikiran Dakwah K.H. Fathul Mu'in Dg. Maggading: Gerakan Muhammadiyah Cabang Makassar 1960-1970 - Syandri Syandri; Azwar Iskandar (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2020)
The Muhammadiyah da'wah movement has continued to develop from year to year, not only in the city of Makassar but has also penetrated remote villages. In Makassar itself, this early movement was headquartered on Banda Street (now Jl. Banda), a place belonging to Daeng Tawiro.This research aims to know: (1) da'wah challenges faced by Muhammadiyah regional leader in 1960-1970 period; and (2) strategic programs of Muhammadiyah Makassar in dealing with da'wah problems. This research is a qualitative descriptive study with library research technique using historical and sociological approaches. The results showed: first, K.H. Fathul Mu'in Dg. Maggading as Chairman of Muhammadiyah Makassar period 1960-1966, faced three major challenges of da'wah at the beginning of his leadership period: (a) the growth of the PKI movement, (b) the dissolution of the Masyumi Party, and (c) paralysis of the Muhammadiyah movement on various lines; Secound, K.H. Fathul Mu'in Dg. Maggading as the pinning of Makassar Muhammadiyah Branch took several strategic steps as an effort to improve among the people, namely: (a) consolidation, (b) stabilization, and (c) promoting development.